An Association of IL-β1, PGj2 Among Patient with First Episode Psychosis (Case-control study) - Mahdi Al Har, Sumeiya; kamil Al Barki, Ali; Hasaan Aldujaili, Arafat (Medical Science Journal for Advance Research, 2022)
Background: A first episode of psychosis is the primary point in time a person experiences a psychotic period. it is frequently very confusing. frightening and distressing, particularly for the reason that it is an unusual experience. unluckily, there are moreover many negative misconceptions and stereotypes linked with psychosis that can additional to one’s distress. Aim of the study Investigate the association between some inflammatory biomarkers with first episode psychosis (FEP) and to find out the correlation with different socio demographic profile Methods: A case-control study was involve patients with first episode psychosis and healthy control. peripheral Blood samples collected from 44 cases they were attending AL-Hakeem General hospital, Psychiatric Department, in the period between January, 2019 to may, 2019. the cases included females and males, and the age was 18-70 years. Control: 44 healthy controls who had no history or clinical evidence of fist episode psychosis or any other disease. Results: revealed that increase in the level of Interlaken β1, and decrease PGJ-2 among FEP patients (1591.8±108.6, and 3.82±0.36) respectively in comparison to control were mean (554.8±54.8, and 9.94±0.67). Conclusion: The inflammatory response is an immune system that allow the individual to cope with various menacing advise, but in long-lasting conditions and pathological, the continuous of this stimulate could develop into harmful. The regulation of the all development involves endogenous counter-balancing mechanisms that control special effects of deleterious pro inflammatory mediators. information showing a misbalance in some pro inflammatory/anti inflammatory in blood of person with FES.